2018
DOI: 10.1016/j.icarus.2017.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Ring faults and ring dikes around the Orientale basin on the Moon

Abstract: Highlights High-resolution GRAIL gravity data reveals the structure of the Orientale basin  Gravity gradients reveal a large ring dike intruded into the Outer Rook ring fault  Crustal thickness models show ring faults extending to the crust-mantle interface

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
47
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 74 publications
5
47
0
Order By: Relevance
“…Both of these characteristics are consistent with normal faults cutting through the crust‐mantle interface (Andrews‐Hanna et al, ; Zuber et al, ). The topography of Orientale's innermost ring, the Inner Rook located at R ≈ 230 km, indicates that it is related to the peak rings of smaller basins (Andrews‐Hanna et al, ; Nahm et al, ).…”
Section: Introductionsupporting
confidence: 66%
See 4 more Smart Citations
“…Both of these characteristics are consistent with normal faults cutting through the crust‐mantle interface (Andrews‐Hanna et al, ; Zuber et al, ). The topography of Orientale's innermost ring, the Inner Rook located at R ≈ 230 km, indicates that it is related to the peak rings of smaller basins (Andrews‐Hanna et al, ; Nahm et al, ).…”
Section: Introductionsupporting
confidence: 66%
“…Johnson et al () found that the Outer Rook and Cordillera, the outer rings of Orientale, are large normal faults that form during crater collapse. These faults offset the crust‐mantle interface and locally thin the crust consistent with constraints from GRAIL gravity (Andrews‐Hanna et al, ; Zuber et al, ). In the simulations of Johnson et al () faults formed as the result of inward flow of warm and weak mantle material during collapse of the transient cavity.…”
Section: Introductionsupporting
confidence: 62%
See 3 more Smart Citations